The role of learning technologists in supporting e-research - Susi Peacock; Ann Robertson; Sarah Williams; Maria Giatsi Clausen (Research in Learning Technology, 2009)
This article explores how the role of learning technologists, a professional group that has emerged during the last 15 to 20 years, may be diversifying to include supporting e-research. It contributes to the current debate about the emerging profession and the roles it should play in contemporary higher education. Previous studies have shown that, typically, the profession's role has focussed almost exclusively on curriculum development; traditionally, learning technologists work with students and tutors to enhance the learning environment with technology. This article presents two case studies of PhD research that used a standard e-learning tool, the virtual learning environment (VLE), to conduct focus groups online. The case studies demonstrate the expert role of the learning technologist in supporting researchers to make informed decisions about whether and how to use e-learning tools to conduct qualitative e-research. The learning technologist advised on the potential advantages and limitations of using the VLE for research and fostered collaborative, working relationships with the researchers, acquiring extensive background knowledge about their projects. This required the learning technologist to draw upon her own experience with research into e-learning and on her professional experience gained from supporting curriculum developments. It is suggested that many learning technologists could extend their roles, transferring their knowledge to include supporting e-research. A more inclusive model of the learning technologist's role in academia could help address the potential polarisation of the profession into researchers and practitioners.